ECONOMIC ACTIVITY-BASED DEVELOPMENT OF ISLAMIC GROUP FORMATION THROUGH BUSINESS COMMUNITY VILLAGE MEKARJAYA - Mukhlis, Zaeni (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Real Working Lecture (KKN) is one form of community service are included in the five dharma University Duanda is implemented in a comprehensive and cross-sectoral. Community work (KKN) Faculty of Islamic Economics (FEI) to implement service learning activities in the village and the village Mekarjaya Kabandungan Kabandungan District of Sukabumi. Meanwhile, the location of KKN group 3 is in Kampung Sorogol RT / RW 06/04 Mekarjaya Rural District of Kabandungan. The village Mekarjaya has an area of 1,901 hectares, with a total of 1063 heads of families, divided into five neighborhoods and 22 hamlets. Kp population. Sorogol most have livelihood as farmers and farm workers. Residents Kp. Sorogol very open and quite active in service learning students follow the whole program. The work program Real Working Lecture (KKN) 3 group is divided into two categories, namely physical and non-physical program. The entire program of work done well and as expected. As there are several obstacles in its implementation and not in accordance with a predetermined schedule, but activity continues to run smoothly and performing well.